Morphological variation and expressed sequence tags-simple sequence repeats-based genetic diversity of Aspergillus cristatus in Chinese dark tea - Hu, Zhiyuan; Liu, Shiquan; Zhou, Xiaohong; Liu, Zhanjun; Li, Taotao; Yu, Songlin; Zhang, Xinyu; Xu, Zhenggang (Frontiers in Microbiology, 2024)
Introduction Aspergillus cristatus is a homothallic fungus that is used in the natural fermentation process of Chinese Fuzhuan tea and has been linked to the production of bioactive components. However, not much is known about the variations present in the fungus. To understand the variation of the dominant microorganism, A. cristatus, within dark tea, the present study investigated the genetic and morphological diversity of 70 A. cristatus collected across six provinces of China. Methods Expressed sequence tags-simple sequence repeats (EST-SSR) loci for A. cristatus were identified and corresponding primers were developed. Subsequently, 15 specimens were selected for PCR amplification. Results The phylogenetic tree obtained revealed four distinct clusters with a genetic similarity coefficient of 0.983, corresponding to previously identified morphological groups. Five strains (A1, A11, B1, D1, and JH1805) with considerable differences in EST-SSR results were selected for further physiological variation investigation. Microstructural examinations revealed no apparent differentiation among the representative strains. However, colony morphology under a range of culture media varied substantially between strains, as did the extracellular enzymatic activity (cellulase, pectinase, protease, and polyphenol oxidase); the data indicate that there are differences in physiological metabolic capacity among A. cristatus strains. Discussion Notably, JH1805, B1, and A11 exhibited higher enzymatic activity, indicating their potential application in the production of genetically improved strains. The findings provide valuable insights into species identification, genetic diversity determination, and marker-assisted breeding strategies for A. cristatus.